Examining the mechanisms for and factors affecting benefit sharing in two South African aquaculture projects - Agiotis, Brett (Environmental Humanities South, 2024)
The Blue Economy, that gained traction at the Rio + 2012 Earth Summit hosted by the United Nations, has been put forward as a concept to fast-track socio-economic development in the ocean space in a way that integrates marine conservation and social equity. Aquaculture is one of the key sectors of the Blue Economy and is seen as a frontier for driving economic growth, enhancing food security, and relieving the pressure of capture fisheries. What remains uncertain is the extent to which these high-level policy interventions translate into benefits for people on the ground who are directly and indirectly affected by them. The aim of this study was to contribute to a better understanding of the perceptions of benefits marginalised individuals and coastal communities in South Africa derive from involvement in Blue Economy projects linked to aquaculture as well as the key factors enabling and inhibiting benefit sharing. In contexts where local people perceive that they benefit from Blue Economy activities, the study unravels whether the distribution of those benefits is seen as fair and equitable. The study used two aquaculture projects implemented in Doringbaai and Saldanha Bay on the West Coast of South Africa as a lens. These aquaculture projects were implemented with the aim of creating jobs, enhancing food security, building skills, and benefiting individuals and the wider community. Findings revealed that despite positive impacts through employment, skills development, and the establishment of aquaculture enterprises, several factors influenced the effectiveness of benefit sharing for individuals and coastal communities leading to negative perceptions regarding these interventions. Unequal power relations, flawed benefit sharing arrangements, and the COVID-19 pandemic had a major impact on benefit sharing outcomes envisaged for both projects. 3 Moreover, while the South African government made considerable effort to support individual and wider coastal community participation in the aquaculture sector, the level of postimplementation support from the state for these projects was lacking. Based on an enhanced understanding of how the projects were executed as well as individual and community perceptions of benefit sharing, this study argues that the nature of benefit sharing arrangements, the institutional arrangements, and power dynamics amongst actors involved in the aquaculture projects can significantly influence the extent to which people benefit. Other factors such as power dynamics, participation, transparency, transfer of skills, post-implementation support, robust institutions, and effective benefit sharing arrangements must be considered in the planning and implementation of Blue Economy projects and programmes. This is vital in order to ensure that aquaculture projects involving individuals and communities can be financially viable, sustainable, and achieve equitable social benefits.